Green Power architecture considerations for rural computing - Sin, Giap Yew; Chong, Eng Tan; Thangaveloo, R. (IEEE, 2012)
The introduction of computer technology has brought revolutionary impacts to the living in rural areas. This technology has narrowed the digital divide between the urban and the rural. However, limitation in electricity supply is the major constraint in powering up the Information and Communications Technologies (ICT) equipment in the rural. Consistent electricity supply has become an obstacle in deploying computing systems in the rural environment. Therefore, green and energy efficient power architecture has been proposed in this paper to reduce power wastage and make efficient use of the power for consumption by ICT equipment in order to prolong the operating time of the equipment. Green power architecture can generally be organized into several areas of application such as power sustainability, energy efficiency and reduction in power loss. The effective use of power provision in rural areas has also been taken into consideration. This paper shows that systems that are direct DC powered, wired networked and use solid state Hard Disk Drive (HDD) are more energy efficient and those are the important parameters for rural computing implementation.